On the Issue of the Radon Activity of Tectonic Faults on the Qatar Peninsula - Ulyanov, V. Y.; Bilyk, V. V. (Science and Transport Progress, 2024)
Purpose. The paper aims at providing the modern evaluation of radon activity in identified tectonic faults of the earth's crust based on archival data of radon measurements in groundwater which previously have been performed in the northern and eastern parts of the Qatar Peninsula. Methodology. The paper presents an additional extended justification for the application of an innovative technique for these conditions to identify the activity rate of tectonic faults in the rock foundation under the geological conditions of the Qatar Peninsula based on third-party measurements of radon in groundwater and using own universal Evaluation scale. Findings. A modern analysis of previously obtained results of radon measurements in groundwater of the Qatar Peninsula allowed us to suggest the orientation of tectonic fault directions in its northern and eastern parts and to additionally reveal the rate of their radon activity within the peninsula with a preliminary magnitude evaluation of displacement along the faults. A similar assumption was also proposed in the western part of the UAE adjacent to the peninsula, where the Barakah Nuclear Power Plant (BNPP) is located. This assumption is based on a certain similarity in the geological and tectonic conditions of the region. Originality. For the first time, the authors proposed the location of tectonic faults within the northern and eastern parts of the Qatar Peninsula according to radonometry performed for other purposes. We estimated their radon activity and the magnitude of movement along the faults. This implies increased safety during the construction and operation of various facilities, including a high degree of responsibility, particularly pipeline systems and transport communications that are important for the country's economy. Practical value. This technique can also be used in seismic monitoring for construction sites and in adjacent territories of other countries where similar explorations have not been conducted before.